2014
DOI: 10.1121/1.4893906
|View full text |Cite
|
Sign up to set email alerts
|

Differences in acoustic features of vocalizations produced by killer whales cross-socialized with bottlenose dolphins

Abstract: Limited previous evidence suggests that killer whales (Orcinus orca) are capable of vocal production learning. However, vocal contextual learning has not been studied, nor the factors promoting learning. Vocalizations were collected from three killer whales with a history of exposure to bottlenose dolphins (Tursiops truncatus) and compared with data from seven killer whales held with conspecifics and nine bottlenose dolphins. The three whales' repertoires were distinguishable by a higher proportion of click tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Many consider whistles as communication or social sounds (Au, 1993;Musser et al, 2014;King and Janik, 2015). Their simultaneous use while searching with sonar clicks suggests that dolphins may be adept at doing two things at once -making decisions about food capture and communicating with other animals in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Many consider whistles as communication or social sounds (Au, 1993;Musser et al, 2014;King and Janik, 2015). Their simultaneous use while searching with sonar clicks suggests that dolphins may be adept at doing two things at once -making decisions about food capture and communicating with other animals in the process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bain (1986) described a 10 year old female captured off Iceland mimicking the calls from a 13 year old female captured in Canada after sharing a tank for several years. Captive killer whales that were housed with bottlenose dolphins were reported to produce dolphin type chirps (Musser et al, 2014). found that a captive killer whale calf learned calls selectively from its mother, but demonstrated that two captive juvenile male killer whales learned new calls and altered their repertoires to match that of an unrelated adult male with whom they were most strongly associated.…”
Section: Vocal Learningmentioning
confidence: 99%
“…usage learning) cannot be completely ruled out without further experiments, the aggregate data from these studies indicate that cetaceans and pinnipeds do exhibit vocal learning. Interestingly, recent data suggest that killer whales can alter their vocalizations to match those of dolphins when the two species socialize (40, 41), and dolphin calls do not appear to be “copied” from a tutor like songbird vocal learning, but rather appear to be unique to each animal (40). Even more remarkable is the evidence that cetaceans that spend time with humans can mimic human speech (42).…”
Section: Vocal Learning: What Is It and Who Has It?mentioning
confidence: 99%